The function of Eriocheir sinensis transferrin and iron in Spiroplasma eriocheiris infection. Issue 79 (August 2018) - Xu, Xuechuan; Liu, Yuhan; Tang, Mengyue; Yan, Yuye; Gu, Wei; Wang, Wen; Meng, Qingguo
Abstract: Transferrin, a member of the iron binding superfamily protein, plays an extremely important role in the transport of iron in the biological process of cells. The result of preliminary proteomic study on E. sinensis hemocytes infected Spiroplasma eriocheiris showed the expression of transferrin ( EsTF ) and ferrin ( EsFe ) significantly changed. In addition, other reports have confirmed that transferrin, ferritin and iron are involved in the immune response of hosts. In order to validate the immune function of EsTF, the whole length of EsTF was successfully amplified by the gene cloning and RACE technique. The results showed that the full-length cDNA of the EsTF gene was 2748 bp, including a 2193 bp open reading frame which encodes 730 amino acids. The result of bioinformatics analysis showed EsTF contains two highly conserved TR_FER domains. Evolutionary analysis showed that EsTF has a close genetic relationship with other TFs of invertebrates. In addition, EsTF mRNA was highly transcripted in nerve and intestine tissues, followed by hemocytes. The expression of EsTF, EsFe1 and EsFe2 increased after exogenous supplemental of iron under the concentration of 100 nmol/L in water. After exogenous supplement of iron and injection with S. eriocheiris, these three gene transcription of mRNA levels were higher than that of PBS group, while lower than the S. eriocheiris group and the iron group. Besides, the copy number of S. eriocheiris in the experimental group was significantly reduced, and the death rate decreased. As can be seen, iron made transferrin and ferritin return to normal levels during the infection of S. eriocheiris and help the host maintain normal immunity levels to resist S. eriocheiris . These results further demonstrated that EsTF, EsFe1, EsFe2 and iron play a role in the immune defense mechanism of the crabs to resist S. eriocheiris infection. Highlights: The whole length of EsTF was successfully amplified. EsTF, EsFe1 and EsFe2 significantly increased during S. eriocheiris challenge. The copies of S. eriocheiris and crabs' death rate were obviously decrease in exogenous iron supplement assay.